Комплекс обрядів викликання та зупинення дощу у румунів Буковини - Мойсей, А. (Народна творчість та етнографія, 2005)
Ritual rites of evocating and stopping the rain by Bukovynian Romanians are under complex study in the given article. “Kaloyan”, “Paparude”, individual ritual rites performed by ordinary peasants and retual rites complex performed by “solomonars” – “contrsolomonars” aiming to evocate and stop the rain are explored in the article as well.